A New Method for Design of Microstrip Line Interdigital Filter - Feng Zhenghe Yu Xiaoguang (Tongxin xuebao)
The paper proposed a numerical method for calculating the characteristic of microwave filter where transmission properties of coupled multi conductor are used directly Not only coupling between adjacent conductor but also non adjacent ones are considered The nonsymmetric coupling structure can be dealt with also So the accuracy of results becomes higher There are many intrinsic modes with different propagation constant in a multiconductor structure filled by many dielectric materials This is quite different from the multiconductor with homogeneous media filled We must consider not only intrinsic impedance but also different propagation constants The intrinsic values and Vectors of Multiconducter transmission line can be got by matrix telegraphist’s equation The characteristic of filter can be expressed by equivalent network after optimized The paper presented some examples including a filter with non-equal width cavities structure to show the validity of this method